Burnout and playing position: a study of Brazilian soccer players - Llopes Vverardi, C. E.; Nagamine, K.; Merussi Neiva, C.; Müller Pessoa Filho, D.; Aparecida Micelli Domingos, N.; Gomes Ciolac, E.; de Oliveira Santos Miyazaki, M. C. (Journal of Physical Education and Sport, 2014)
The objective of the present study was to identify and compare benchmarks for burnout in relation to variables such as: professional and amateur players, and game position during the preparation phase. Participated in this study 134 male soccer players: 71 professional players (age=22.77±3.98 years) and 63 amateur players (age=17.18±0.84 years) of three teams of Campeonato Paulista (Series A-1 and A-2) and Copa São Paulo de Futebol Júnior, in São Paulo, Brazil. Athlete Burnout Questionnaire (ABQ) was used to assess burnout syndrome. Professional goalkeepers and forwards players and amateur defenders and presented the highest total average scores for burnout, associated with the physical and emotional exhaustion. When comparing professional and amateur players in relation to the playing position, not showed significant difference with regard to scores of burnout in its three dimensions.